2023
DOI: 10.29333/ejgm/12855
|View full text |Cite
|
Sign up to set email alerts
|

Association of abdominal obesity and systolic blood pressure indices with cardiovascular disease risk prediction among community-dwelling older adults

Abstract: <b>Background:</b> Excess adiposity is an established risk factor for cardiovascular disease (CVD), therefore the early screening indies with predicted CVD risk is more useful for older adults. The current study evaluated the associations between anthropometric, body composition and dietary indices and elevated 10-year CVD risk in older people.<br /> <b>Methods:</b> This research, which involved 55 to 94-year-olds living in the community. Standard techniques were used to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…In a prospective study by Ma et al a strong positive association was reported between mean SBP and CVD risk [34]. Duangjai et al, showed that higher SBP and DBP was associated with a strong positive association with CVD risk prediction score [35]. The study by Liszka et al also found a positive association between BP and risk of CVDs [36], including arteriosclerotic disease, congestive heart failure Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a prospective study by Ma et al a strong positive association was reported between mean SBP and CVD risk [34]. Duangjai et al, showed that higher SBP and DBP was associated with a strong positive association with CVD risk prediction score [35]. The study by Liszka et al also found a positive association between BP and risk of CVDs [36], including arteriosclerotic disease, congestive heart failure Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The results showed that in people with MetS, measures of central obesity showed no association with 10-year risk of CVD, however, it is likely that the impact of central obesity on CVD risk at least partly is mediated through lipids, elevated BP, and blood glucose, and the current study may have over-adjusted by including intermediate factors in the multiple model. Duangjai et al, showed that there was a strong positive association between WC and CVD risk prediction score [35]. Also, body mass index (BMI) has a strong association with higher prevalence of CVD independent of MetS [41].…”
Section: Discussionmentioning
confidence: 99%